The Resilience of Urban Kampong Community in the Aftermath of the Pandemic - Lutfi Amiruddin; Iwan Nurhadi (University of Muhammadiyah Malang, 2024)
The impacts of the Covid-19 Pandemic have struck the economic and public health of urban residents. As a community who live in densely populated areas around Pasar Besar Malang, kampong inhabitants must cope with the outbreak as well as recover in the aftermath the pandemic using their own resources. This article investigated the role of the collective memory contributed to forming local knowledge to make the best way to deal with the pandemic turbulences as well as how people started to initiate resilience using the urban infrastructure resources in post-outbreak. Utilizing the qualitative method, the results show two essential findings. First, the collective memory of the past plague was absent in communities’ everyday life for a long time of period which made people have no simple guidance to overcome the pandemic impacts. The politics of ethnic segregation in housing during Colonial Era contribute for keeping distance people from the outbreak history. Second, several urban infrastructures such as clean water supply and public electricity which were properly provided for kampong community devoted in composing resilience during until after the pandemic. Ultimately, using those physical infrastructures the social structures were transformed.